2022
DOI: 10.3389/fendo.2022.777868
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin Expression and Actions in Pancreatic β-Cells

Abstract: Pleiotrophin (PTN) is a heparin-binding cytokine that is widely expressed during early development and increases in maternal circulation during pregnancy.Aged PTN-deficient mice exhibit insulin resistance, suggesting a role in metabolic control. The objectives of this study were to determine if PTN is expressed in mouse pancreatic β-cells in young vs. adult animals, and its effects on DNA synthesis, β-cell gene expression and glucose-stimulated insulin secretion (GSIS). The Ptn gene was expressed in isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In humans, circulating PTN levels are significantly associated with advancing chronological age, what confirms a retention of pleiotrophin expression in adult tissues (8). In particular, a residual expression of pleiotrophin has been found in the adult liver, brain, adipose tissue, testis, and pancreas (9)(10)(11).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In humans, circulating PTN levels are significantly associated with advancing chronological age, what confirms a retention of pleiotrophin expression in adult tissues (8). In particular, a residual expression of pleiotrophin has been found in the adult liver, brain, adipose tissue, testis, and pancreas (9)(10)(11).…”
Section: Introductionmentioning
confidence: 62%
“…Pancreatic b cells share with neurons that are excitable cells (95) and that retain high levels of Ptn expression in the adult. In fact, PTN maintains a high level of expression in the b cells of pancreatic islets of adult rats [10], mice [10] and humans [10]. The expression of Ptn in b cells could potentially contribute to adaptive increases in b cell mass as PTN is prominently expressed in Ins + Glut LO 2 cells, the immature pancreatic b cells that have multipotential islet endocrine cell lineage potentiality, and retain the proliferative capacity (10).…”
Section: Pleiotrophin and Pancreas: The Pancreatic Beta Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also showed that, in contrast to the effect of LDL and VLDL, HDL prevents the release and invigoration of proapoptotic molecules in the beta cells of the pancreas. In addition, several peptides, including but not limited to apelin, pleiotrophin, ghrelin and urocortin have also been detected in the beta cells of the pancreas [ 27 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resp18 is upregulated in islets by exposure to high glucose and in islets of diabetic NOD mice, and it shares a partial sequence homology with IA-2, which is a dense-core secretory vesicle protein that helps facilitate insulin secretion ( 64 ). The Ptn gene product pleiotrophin is a secreted heparin-binding cytokine that is of interest because of its capacity to promote angiogenesis, act as a protooncogene, stimulate cell differentiation, and induce proliferation of several cell types, including β cell–derived cell lines ( 66 , 67 ). Intense pleiotrophin expression is observed during β cell regeneration following STZ-induced β cell depletion in mice ( 67 ).…”
Section: Discussionmentioning
confidence: 99%